2022
DOI: 10.1007/s12072-022-10364-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and liver involvement

Abstract: The COVID-19 pandemic is the largest public health challenge in living memory. Patients with underlying liver disease have been disproportionately affected, experiencing high morbidity and mortality. In addition, elevated liver enzymes appear to be a risk factor for disease progression, even in the absence of underlying liver disease. Nevertheless, the mechanism of liver injury in SARS-CoV-2 infection remains largely unknown. This review aims to provide an overview of the mechanisms by which SARS-CoV-2 induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 63 publications
1
44
0
3
Order By: Relevance
“…The main biochemical abnormality detected is an elevation in aminotransferase levels, often mild, observed in more than 20% of cases, with a subsequent minimal increase in bilirubin levels (10% of patients), while the increase in gamma-glutamyl transferase and alkaline phosphatase is uncommon [ 2 , 5 ]. Liver damage is not responsible for high mortality or severe illness in patients with SARS-CoV-2 infection, but it seems that COVID-19 infection may affect liver disease progression [ 6 ]. The main mechanism is linked to an exaggerated release of inflammatory cytokines and the activation of the inflammasome pathway in target cells, following SARS-CoV-2 infection, mostly in patients with cirrhosis [ 6 ].…”
Section: Risks Of Covid-19 and Serious Illness From Covid-19 In Patie...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main biochemical abnormality detected is an elevation in aminotransferase levels, often mild, observed in more than 20% of cases, with a subsequent minimal increase in bilirubin levels (10% of patients), while the increase in gamma-glutamyl transferase and alkaline phosphatase is uncommon [ 2 , 5 ]. Liver damage is not responsible for high mortality or severe illness in patients with SARS-CoV-2 infection, but it seems that COVID-19 infection may affect liver disease progression [ 6 ]. The main mechanism is linked to an exaggerated release of inflammatory cytokines and the activation of the inflammasome pathway in target cells, following SARS-CoV-2 infection, mostly in patients with cirrhosis [ 6 ].…”
Section: Risks Of Covid-19 and Serious Illness From Covid-19 In Patie...mentioning
confidence: 99%
“…Liver damage is not responsible for high mortality or severe illness in patients with SARS-CoV-2 infection, but it seems that COVID-19 infection may affect liver disease progression [ 6 ]. The main mechanism is linked to an exaggerated release of inflammatory cytokines and the activation of the inflammasome pathway in target cells, following SARS-CoV-2 infection, mostly in patients with cirrhosis [ 6 ]. In particular, patients with cirrhosis have high overall mortality for COVID-19 (32%), increasing with each Child–Pugh class (patients with CLD without cirrhosis, as well as general population: 8%, Child–Pugh A 19%, Child–Pugh B 35%, Child–Pugh C 51%) [ 7 ].…”
Section: Risks Of Covid-19 and Serious Illness From Covid-19 In Patie...mentioning
confidence: 99%
“…COVID-19 associated liver injury is defined as liver injury directly due to the virus or its treatment in patients with or without preexisting liver damage[ 29 ]. The exact mechanism of liver injury in the presence of SARS-CoV-2 infection is largely unknown[ 30 ]. It has been described that this virus enters the cell through angiotensin converting enzyme 2 (ACE2) receptors, which are abundant in many areas of the body, including cholangiocytes and hepatocytes.…”
Section: Sars-cov-2 Effects On the Livermentioning
confidence: 99%
“…In addition, a direct relationship between the grade of liver injury and severity of the disease has been established[ 33 ]. Elevated liver enzymes appear to be a risk factor for disease progression, even in the absence of underlying liver disease[ 30 ]. Mild aspartate transaminase (AST) elevation is considered an early sign of severe COVID-19, while high alanine transaminase (ALT) levels are considered an independent predictor of prolonged SARS-CoV-2 RNA shedding.…”
Section: Sars-cov-2 Effects On the Livermentioning
confidence: 99%
“…[3][4][5][6] While the impact of COVID-19 on the liver remains unclear, a considerable proportion of patients with elevated liver enzyme have been reported. [6][7][8] Some studies found a mild [1-2 times the upper limit of normal (ULN)] increase in transaminases, while severe liver injury has also been reported. 3,9,10 However, information related to the clinical course of COVID-19 patients with liver injury is very limited, especially in severe and critical patients.…”
Section: Introductionmentioning
confidence: 99%